The Association Between FokI Vitamin D Receptor Polymorphisms With Metabolic Syndrome Among Pregnant Arab Women - Alzaim, Maysa; Al-Daghri, Nasser M.; Sabico, Shaun; Fouda, Mona A.; Al-Musharaf, Sara; Khattak, Malak N. K.; Mohammed, Abdul Khader; Al-Ajlan, Abdulrahman; Binjawhar, Dalal N.; Wood, Richard (Frontiers in Endocrinology, 2022)
Metabolic syndrome (MetS) is a serious health condition that is becoming extremely threatening in Saudi Arabia. The link between vitamin D receptor (VDR) gene polymorphisms and maternal MetS has been observed in several ethnic groups, but is yet to be clarified in the Arabian population. This study aims to investigate the relationship between the FokI VDR genotype and the risk of MetS and its components in pregnant Saudi women. A cross-sectional study was conducted using 368 pregnant Saudi women on first trimester screened for MetS (44 with MetS and 324 without MetS). Measurements included anthropometrics, glycemic and lipid profile and 25(OH)D. Allele-specific polymerase chain reaction was used to determine Fokl VDR genotype of participants. Vitamin D deficiency (25(OH)D <50nmol/l) was seen in 85% of the participants. An estimated 12% of participants had MetS. In the MetS group, the FokI VDR genotyping frequencies for FF, Ff, and ff genotypes were 50%, 36.4% and 13.6% (6), respectively. In controls, the frequencies were 62.7%, 31.5% and 5.9%, respectively. No significant association between the individual MetS components and FokI VDR genotypes were observed. Nevertheless, carriers of the ff allele had a significant risk for full maternal MetS [Odds Ratio 4.2 (95% Confidence Interval 1.4-12.2; adjusted p=0.009). The study suggests that the ff FokI VDR genotype is a genetic marker of maternal MetS in pregnant Arabian women. Prospective studies that include neonatal outcomes may confirm present findings.